Order of superconductive phase transition - Kleinert, H. (Condensed Matter Physics, 2005)
On the occasion of Reinhard Folk’s 60th birthday, I give a brief review of
the theoretical progress in understanding the critical properties of superconductors.
I point out the theoretical difficulties in finding a second-order
transition in the Ginzburg-Landau Model with O(N)-symmetry in 4 − ε Dimensions,
and the success in predicting the existence and location of a
tricritical point with the help of a dual disorder theory. З нагоди 60-річчя Райнгарда Фолька я приводжу короткий опис теоретичного прогресу в розумінні критичних властивостей надпровідників. Я відзначаю теоретичні труднощі у виявленні фазового переходу другого роду в O(N) симетричній моделі Гінзбурга-Ландау в вимірності 4 − ε, а також успіх в передбаченні його існування і визначенні трикритичної точки за допомогою дуальної невпорядкованої теорії